Análisis jurídico del arbitraje y mediación en la resolución de conflictos civiles en la ciudad de Huaquillas en el año 2012. - Córdova Armijos, Linda Leovanna (2014)
This thesis has been developed according to the guidelines of the field research, and therefore is both quantitative and qualitative. The main source of information are surveys of lawyers, students and community.